RECENT TRENDS IN DENGUE DETECTION METHODS USING BIOSENSORS - AHMAD ANWAR ZAINUDDIN; ANIS NURASHIKIN NORDIN; ROSMINAZUIN AB RAHIM (International Islamic University Malaysia Engineering Journal, 2018)
ABSTRACT: Dengue illness is an infectious tropical disease, transmitted by Aedes mosquitos, that poses a serious health threat to the tropical world. This disease causes widespread infection worldwide, with about 50 million cases of dengue occurring per annum out of which 500,000 recorded cases of dengue hemorrhagic fever and 22,000 deaths.  Currently, there are no effective vaccines available to prevent the spread of the infection. Accurate and rapid laboratory diagnostic tests are required for early detection to reduce patient mortality rate. In this paper,  common laboratory diagnosis methods for detecting dengue virus infection are discussed. Currently, virus isolation, RT-PCR and serology methods provide the most direct and accurate response for detection of dengue. However, these methods require tedious steps, expensive requirements and expert staffs. Recent research have proposed the usage of biosensors as an alternative new technology for detection of dengue. In this work, various types of biosensors such as electrochemical, piezoelectric, and optical biosensor have been described and compared to evaluate their effectiveness in dengue detection.  It is observed that the optical biosensor offers the best detection due to its high sensitivity as compared to others, although it is popularly known as an expensive method. Alternatively, the use of electrochemical and piezoelectric biosensors (QCM) is highly recommended for detection of dengue due to their ease-of-use, low cost, low reagent consumption, disposability, and minimal sample preparation. These approaches have the potential to improve the rate of survival, particularly in resource-limited countries.